Gamma-Carboxylation and Fragmentation of Osteocalcin in Human Serum Defined by Mass Spectrometry - Rehder, Douglas S. (Mol Cell Proteomics, 2015)
Serum osteocalcin (Oc) concentration is a highly specific measure of bone turnover, but its circulating proteoform(s) have not been well defined. Based on immunological methods, the major forms are thought to be the intact polypeptide and a large N-terminal-mid molecule fragment for which there is no consensus on the precise sequence. Vitamin K-dependent gamma (γ)-carboxylated variants of Oc are also found in circulation but there have been no methods that can define how many of the three potential γ-carboxyglutamic acid (Gla) residues are γ-carboxylated or provide their relative abundances. Recent reports that uncarboxylated and partially γ-carboxylated Oc forms have hormonal function underscore the need for precise evaluation of Oc at all three potential γ-carboxylation sites. Herein, mass spectrometric immunoassay (MSIA) was used to provide qualitative and semiquantitative (relative percent abundance) information on Oc molecular variants as they exist in individual plasma and serum samples. Following verification that observable Oc proteoforms were accurately assigned and not simply ex vivo artifacts, MALDI-MSIA and ESI-MSIA were used to assess the relative abundance of Oc truncation and γ-carboxylation, respectively, in plasma from 130 patients enrolled in vitamin K supplementation trials. Human Oc was found to circulate in over a dozen truncated forms with each of these displaying anywhere from 0–3 Gla residues. The relative abundance of truncated forms was consistent and unaffected by vitamin K supplementation. In contrast, when compared with placebo, vitamin K supplementation dramatically increased the fractional abundance of Oc with three Gla residues, corresponding to a decrease in the fractional abundance of Oc with zero Gla residues. These findings unequivocally document that increased vitamin K intake reduces the uncarboxylated form of Oc. Several reports of a positive effect of vitamin K intake on insulin sensitivity in humans have shown that un- or undercarboxylation of Oc, unlike in mice, is not associated with insulin resistance. Analyses similar to those described here will be useful to understand the functional significance of Oc γ-carboxylation in human health and disease.